Phonetic Accommodation of Monophthong in the Utterances of In Bruges’ Main Characters - Azizah, Mutia; Pradipta, Bramantya (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
Phonetic accommodation refers to how speakers adjust their pronunciation during interaction, either by becoming more similar (convergence) or more different (divergence). This study investigates phonetic accommodation between two main characters, Ray and Ken, in the movie In Bruges. It explores the types of accommodation that occur, how their accent differences (Irish English vs. British English) influence the process, and whether their speech reflects experimental behavior. The analysis focuses on 50 utterances containing monophthong vowels, examined acoustically using Praat to measure formant frequencies (F1, F2, F3). Contextual factors such as emotion, conversational stance, and scene dynamics were also considered. Findings reveal that divergence is more frequent than convergence. Ray shows phonetic accommodation in 23 utterances (3 convergence), while Ken shows 27 (also 3 convergence). Most convergence is partial, typically involving shifts in only one formant. Ray consistently retains his Irish accent, especially in back vowels, while Ken occasionally deviates from Standard Southern British English norms. Convergence tends to appear in emotionally neutral interactions. Overall, the study suggests that even scripted movie dialogue can reflect natural phonetic accommodation, shaped by accent, identity, emotional tone, and interactional context. Keywords: formant, In Bruges, monophthong, phonetic accommodation, vowel